Influence of grain morphology and orientation on saturation magnetostriction of polycrystalline Terfenol-D. (1st September 2022) - Nieves, P.; Legut, D.
Abstract: In this work we computationally study the effect of microstructure on saturation magnetostriction of Terfenol-D (Tb 0 . 27 Dy 0 . 73 Fe 2 ) by means of Finite Element Method. The model is based on the equilibrium magnetoelastic strain tensor at magnetic saturation, and shows that the crystal orientation jointly with the grain volume fraction play a more significant role on saturation magnetostriction than the morphology of the grains. We also calculate the dependence of saturation magnetostriction on the dispersion angle of the distribution of grains in the oriented growth crystal directions < 011 > and < 111 >, finding that not highly oriented grain distributions reduce saturation magnetostriction significantly. This result evinces the importance of high-quality control of grain orientation in the synthesis of grain-aligned polycrystalline Terfenol-D, and provides a quantitative estimation for the range of acceptable values for the dispersion angle of the distribution of the oriented grains. Highlights: Grain orientation and morphology effects on Terfenol-D. Computational study of saturation magnetostriction via a simplified Finite Element Method approach. Analysis of microstructure deformation due to magnetostriction. Correlation between the dispersion angle of the distribution of the oriented grains and magnetostriction.